Mechanisms of forward current transport in p-GaSe-n-InSe heterojunctions - Kovalyuk, Z.D.; Makhniy, V.P.; Yanchuk, O.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Voltage-current characteristics forwardly biased heterojunctions p-GaSe-n-InSe made by the method of optical contact are analyzed. Asit was ascertained, the forward current is determined by tunnel-recombination processes at low voltages and overbarrier emission. The experimental characteristics are defined by the known theoretical expressions for anisotipical heterojunctions with the energy diagram by Andersen.